2016
DOI: 10.1107/s2052252515018722
|View full text |Cite
|
Sign up to set email alerts
|

Total scattering and pair distribution function analysis in modelling disorder in PZN (PbZn1/3Nb2/3O3)

Abstract: The ability of the pair distribution function (PDF) analysis of total scattering (TS) from a powder to determine the local ordering in ferroelectric PZN (PbZn 1/3 Nb 2/3 O 3 ) has been explored by comparison with a model established using single-crystal diffuse scattering (SCDS). While X-ray PDF analysis is discussed, the focus is on neutron diffraction results because of the greater extent of the data and the sensitivity of the neutron to oxygen atoms, the behaviour of which is important in PZN. The PDF was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Modern synchrotron radiation sources have led to an increasing number of cases in which diffraction and scattering can reach atomic resolution measurement (Codling et al, 2013;Keen & Goodwin, 2015). At the atomic resolution, the structure models can include the atomic anisotropic displacement parameters (ADPs) for individual atoms (Merritt, 1999;Whitfield et al, 2016). The ADPs represent atomic motions and static displacement disorder of the crystal structure, which is important to understand the physical behavior of crystals (Trueblood et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern synchrotron radiation sources have led to an increasing number of cases in which diffraction and scattering can reach atomic resolution measurement (Codling et al, 2013;Keen & Goodwin, 2015). At the atomic resolution, the structure models can include the atomic anisotropic displacement parameters (ADPs) for individual atoms (Merritt, 1999;Whitfield et al, 2016). The ADPs represent atomic motions and static displacement disorder of the crystal structure, which is important to understand the physical behavior of crystals (Trueblood et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse scattering influences the shape and broadness of PDF peaks (Proffen et al, 2005;Egami & Billinge, 2003;Masadeh, 2016). Whitfield et al (2016) reported that the PDF method appears to be sensitive to the ADPs and is clearly more quantitative than single-crystal diffuse scattering when refining the magnitudes of ADPs. Therefore, the PDF refinement has great potential to provide high quality ADPs for a crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…This allows elucidation of SRO that is anisotropic or only affects small regions of reciprocal space. Similarly, the use of pair distribution function and powder diffraction is not discussed, though both are very important techniques [3,18,19,32].…”
Section: Data Collectionmentioning
confidence: 99%
“…When contrast between scatterers is weak (atoms nearby on the periodic table will have very similar X-ray scattering factors), it may be necessary to use neutron and/or X-ray single-crystal diffuse scattering (SCDS) data. Neutron diffraction requires larger crystals, which may be difficult to obtain, so it may be that X-ray SCDS is coupled with neutron pair distribution function analysis (PDF; [18][19][20]), obtained from polycrystalline specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Several articles describe the role of PDF analyses in structural studies of disordered materials. Whitfield et al (2016) examine the perennially important topic of cation displacements in perovskite structured ferroelectrics, focusing on the widely studied PZN [(Pb/Zn)NbO 3 ]. They show how PDF data from powders yield valuable information on lead cation displacements, while at the same time finding that such analyses could not distinguish some of the features that could be observed in analyses of single-crystal diffuse-scattering (SCDS) data.…”
mentioning
confidence: 99%